Trade credit: A benefit to get, a "must" to give? Motives behind trade credit use in Poland - Magda Ciżkowicz-Pękała (e-Finanse: Financial Internet Quarterly, 2017)
The paper analyses the motives behind trade use credit in the Polish enterprise sector, based on the results of the 2016 NBP Annual Survey. It verifies the conclusions stemming from trade credit theories regarding both the main motives driving supply and demand for trade credit, as well as explaining the variation in their relevance across companies. The analysis shows that trade credit supply in Poland is driven to a large extent by suppliers' desire to win and maintain their customers: allowing deferred payments creates attractive terms of sale and is often a requirement set by clients with strong bargaining power. These results indicate high willingness of customers to settle their payments on a deferred basis, which could mirror an important fact uncovered by the survey: contrary to the assumptions made in many theories, trade credit proves to be a relatively cheap form of financing for the majority of the surveyed firms. As a consequence, trade credit could be perceived by firms as an attractive, standard tool used in day-to-day business rather than an expensive form of financing used only to address specific problems or achieve other benefits that would outweigh its high costs. Survey results provide some confirmation for this explanation of trade credit demand.
Keywords: G30; L20; 330; Trade credit; Corporate finance